MODERNIZATION OF LOCAL ECONOMIC MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT: THE ROLE OF LOCAL SELF-GOVERNMENT BODIES (INNOVATIVE ECONOMY, 2026)
Bohach Yu.A., Smoliarov A.S. MODERNIZATION OF LOCAL ECONOMIC MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT: THE ROLE OF LOCAL SELF-GOVERNMENT BODIESPurpose. The aim of this article is to substantiate the role of local self-government bodies in the process of modernizing the local economy in the context of sustainable development and to identify the key areas and mechanisms through which they influence the development of local communities.Methodology of research. The study was conducted using systemic, institutional, structural and functional approaches, which made it possible to view the local economy as a complex multilevel system and to substantiate the role of local self-government bodies in the processes of its modernization in the context of sustainable development. The study employed general scientific and specialized methods, including analysis and synthesis, the comparative method, as well as content analysis of regulatory, legal and strategic documents. A synthesis of the practices of territorial communities in the Ternopil region and an analysis of sociological research results ensured the comprehensiveness, applied orientation and reliability of the findings.Findings. It is substantiated that the modernization of local economic management in the context of sustainable development is a systemic process that goes beyond purely economic growth and encompasses institutional, infrastructural, environmental and managerial transformations at the local level. It has been demonstrated that the effective combination of strategic and spatial planning, program-targeted and project management, economic and environmental incentives, public and private partnerships, grant mechanisms and public monitoring creates the conditions for a transition from fragmented management decisions to a systemic model of sustainable development for territorial communities. The practice of territorial communities in the Ternopil region confirms the feasibility of applying such tools in the process of modernizing the local economy.Originality. A clear distinction has been established between the concepts of “modernization of the local economy” and “local economic development,” which, unlike existing approaches, helps to avoid methodological confusion and enhances the analytical clarity of research in the field of territorial development. The systematization of the main directions of local economic modernization in accordance with sustainable development goals has been improved, allowing for a comprehensive alignment of the strategic development priorities of territorial communities with global sustainable development priorities. The rationale for the role of local self-government bodies as key actors in modernization processes has been further developed, contributing to the increased effectiveness of management decisions at the local level. An original analytical table has been developed that integrates modernization directions, corresponding SDGs, key challenges of territorial communities, and relevant management tools of local self-government bodies, ensuring the practical orientation and applied nature of the research.Practical value. The results of this conducted study can be used by local governments to identify and implement priority areas for modernizing the local economy, as well as to improve governance mechanisms in the context of sustainable development of local communities. In particular, local governments can apply the findings to enhance their institutional capacity, substantiate the strategic decisions, and formulate effective local development policies focused on long-term socioeconomic and environmental sustainability.Key words: Local economy; modernization of the local economy; sustainable development; local self-government bodies; institutional capacity; local economic development; sustainable development goals; circular economy; public and private partnership.
Keywords: Local economy; modernization of the local economy; sustainable development; local self-government bodies; institutional capacity; local economic development; sustainable development goals; circular economy; public and private partnership